PEMERIKSAAN FARMAKOGNOSTIK DAN PROFIL KROMATOGRAFI LAPIS TIPIS TUMBUHAN BAGORE (Caesalpinia crista Linn) ASAL DAERAH POLEWALI MANDAR SULAWESI BARAT - Risda Waris (As-Syifaa Jurnal Farmasi, 2011)
Pharmacognostic assay and using thin layer chromatography of Bagore plant (Caesalpinia crista, Linn).The morphology showed Bagore was the dycotiledonae with woody bark. Transverse section leaves indicated there are stomata anisositik. Transverse section of bark  showed open kolateral.                Physic measurement was including total ash level measurement 6,24 % and undissolved acid ass level equal to 0,55 %. Ekstraction level measurement which included dissolved water extraction level 73,69 % and dissolved etanol ectraction level equals 36,24 %. It was countaining steroid compounds.                Thin layer chromatography result with specific reagent that is on Lieberman-Bouchard reagent after sprayed showed violet this showed positifely countaining steroid compound groupKey word : Bagore(Caesalpinia crista Linn), identification, juice content, ash level.